Keefektifan Penggunaan Media Lagu dalam Pembelajaran Menulis Puisi Siswa Kelas IX1 SMPN 5 Lubuk Basung - Handayati, Wiwit; R., Syahrul; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were to describe the effectiveness of using song media in poetry writing skill for IX1 SMP N 5 Lubuk Basung students. The data of this study were from the result of poetry writing skill pre-test and post-test by using song media in IX1 SMP N 5 Lubuk Basung. Based on the result of data analysis and discussion, it can be concluded that (1) poetry writing skill of IX1 SMP N 5 Lubuk Basung students without using song media with average 58,33, and (2) poetry writing skill of IX1 SMP N 5 Lubuk Basung students by using song media with average 72,26.